Auditor Indepedence as the Dominant Determinant of Audit Quality: Empirical Evidence from Public Accounting Firms in Palembang City - Gita Parera; Sahila; Riza Syahputera (Journal of Economic Studies, 2026)
This study aims to analyze the effects of Time Budget Pressure, Auditor Workload, and Auditor Independence on Audit Quality at Public Accounting Firms (KAPs) in Palembang City, both simultaneously and partially. The study employed a quantitative approach with an associative research design. The sample comprised 45 auditors selected using purposive sampling. Primary data were collected through a Likert-scale questionnaire and analyzed using IBM SPSS Statistics version 26. The results show that Time Budget Pressure, Auditor Workload, and Auditor Independence jointly have a significant effect on Audit Quality. Partially, Time Budget Pressure and Auditor Workload do not significantly affect Audit Quality, whereas Auditor Independence has a positive and significant effect and is the most dominant variable. The adjusted R² value of 0.783 indicates that 78.3% of the variation in Audit Quality is explained by the three independent variables, while the remaining 21.7% is explained by factors outside the research model. These findings underscore the important role of auditor independence in improving audit quality at Public Accounting Firms in Palembang City.